Juan Bartolomé: in the footsteps of B. Cabrera, C. J. Gorter, and L. Néel - Fruchart, Daniel (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2024)
Forewords Interestingly, in the proceedings of the “Institut International de Cooperation Intellectuelle” the meeting “Réunion d’Etudes sur le Magnétisme” helded in Strasbourg, 21–25 May 1939 [1], one can find the successive contributions of C. J. Gorter (p. 57), L. Néel (p. 58), and B. Cabrera (p. 59). The Dutch scientist is known having contributed merely on paramagnetism and relaxation, the French scientist, having focused on the molecular field, sending out the basis of antiferromagnetism and the Spanish, the oldest, was of the pioneers and productive scientists in terms of magnetic properties. Indeed, the main concern of those physicists and their distinguished colleagues was to better understand the behavior of magnetic materials versus temperature, pressure, alloying combinations… So they aimed to introduce the necessary thermodynamic considerations in stabilizing magnetic couplings. Graduated in Physics in 1971, Juan Bartolomé passed his PhD thesis in 1975 under the supervision of Pr. Domingo Gonzales at the University of Zaragoza (Spain) devoted to librational motion and distortion in fluoride-type perovskites (NH4)MF3 and their physical properties using namely specific heat measurements. Then, he enjoyed a postdoctoral fellowship at the Kamerlingh Onnes Laboratorium (just before directed by C. J. Gorter) in Leiden, Netherlands. There, Juan was working with Prof. Jos L. de Jongh on the low-temperature physics of magnetic systems. During the International Conference on Magnetism, ICM76’ held in Amsterdam, when presenting my own PhD poster dedicated to “Magnetic properties of metal perovskite Mn3MX (M = metal, X = C, N)”, I was suddenly called into question by four smiling zaragozanes scientists Domingo Gonzales, Rafael Navarro, Ramon Burriel, and Juan Bartolomé. They wondered to know lot about these non-conventional types of magnetic perovskites. So, I was bombarded with questions. But the contact was made so fair that immediately we decided to collaborate, so establishing future works in link with the Laboratoire de Cristallographie (further integrated in the Institut Néel) at Grenoble, France. Juan has accepted promptly being the responsible scientist for this bridge, since returning to Zaragoza in 1977. The aim of this cooperation was first to relate the phase diagram, structure, and experimental magnetic analyses of the Mn3MX series with most extended thermodynamic, magnetic investigations, then enabling more fundamental up to theoretical knowledge. After his return to Spain, Juan taught General Physics and Thermodynamics at the University of Zaragoza. In 1984–85 he contributed in a decisive way to the creation of the Institute of Materials Science of Aragón (ICMA) as a joint center of the Spanish Consejo Superior de Investigaciones Científicas (CSIC) and the University of Zaragoza. Juan served as the second Director of the ICMA (1987–91), coinciding with his appointment as Full Professor by the CSIC. Then, Juan was elected member of the Panel for New Materials of the Ministry of Industry, which created several CSIC centers on Materials Science. At the time Juan launched a tremendous effort in refurbishing the ancient building of the ICMA, in erecting new and modern buildings and parallel in acquiring numerous and advanced research instruments. 2. Back to projects Parallel to his personal and various research interests, we hardly worked with Juan and his group on: – the Mn3MX series of magnetic carbides and nitrides, namely those exhibiting unusual triangular spin configurations (now revived exhibiting large anomalous Hall effect in thin films), – the MM’X series of ternary transition metal pnictides with X = P or As (for which high magnetocaloric effect was evidenced more recently), – the exceptionally hard magnetic materials of type RE2Fe14B, and other type REFe12–xMx with RE = Rare Earth metal. Further, for the latter topic and with his research team, Juan has developed one of the most interesting contributions in European actions. He critically studied the domain wall relaxation thermodynamics previously misinterpreted as First Order Magnetic Processes. Additionally, he mastered equations governing the various spin reorientation processes (SRP) encountered in the three here-above mentioned series of magnetic materials. Parallel, thanks to the many exchanges and venues in Grenoble between 1979 and 1990, (supported by two Actions Intégrées, Programme International de Coopération Scientifique, grants Postes Rouges CNRS and PAST-Université) Juan has used and gauged the rich benefit of neutron scattering to magnetic materials sciences, as he early performed at Siloé reactor (CEA) initiated by L. Néel. Soon, Juan was part of a small group of pioneers who boosted through their own research, the Spanish participation to the European neutron sources. In fact, soon he was convinced by the “sister” large instrument technique, the Synchrotron Radiation Facility, through early cooperation with the Frascati Laboratory (Italy). So after the 85’, having exerted one’s efforts to joint Spain as a member of Institute Laue Langevin (ILL), Juan was again the distinguished architect acting to associate Spain with the European Synchrotron Research Facilities. Later, he was elected a member of the ESRF Administration Council and the Scientific Advisory Committee. Then, broadening again his research interests, namely to high-temperature superconducting compounds and molecular magnetism, he has acted strongly to create the first Laboratoire International Associé (LIA CNRS–CSIC), liking ICMA, Zaragoza and Laboratoire de Cristallographie, Grenoble. Accordingly, the LIA MA.NE.S for Magnetism–Neutron–Synchrotron (1993–2001) was headed by Pr. Juan Bartolomé for the first half period. To complete on this intense bi-lateral cooperation period, one has to retain that at least 100 resulting papers were published mostly in high-impact journals. The publications have involved more than 25 visiting scientists, among them 11 co-supervised PhD, as well as several post-docs and master students. Moreover, a low-temperature ac susceptometer was developed in Zaragoza for Grenoble and reciprocally a high-temperature paramagnetic torque was developed in Grenoble for Zaragoza. 3. Magnetism from all angles However, these are some parts only of the prolific career of the scientist Juan Bartolomé which covers a wide range of subjects on experimental and theoretical magnetism and its thermodynamics. Among the various top investigations that Juan has developed parallel, one has to underline: (1) Experimental evidence of macroscopic resonant quantum tunneling at magnetization (published in Nature); (2) Specific heat of relaxing single molecule magnets and the study of field-induced quantum relaxation processes; (3) Study of thermodynamics and statistical mechanics of the magnetic ordering in 2- and 1-dimensionality model systems; (4) Magnetism (magnetic moment and anisotropy) of nanoparticles, in relation with their size, structure, and environment; (5) In collaboration with industry, the design of a permanent magnet brushless motor also including the effects of corrosion on motors. In fine, Juan published over 400 articles mostly in top-level international journals, he supervised close to 20 PhD works, he contributed to several international schools and chaired the EMMA’98 (European Conference on Magnetic Materials and Applications…. the 1st held in 1970, Laboratoire de Magnétisme, L. Néel) and the SCTE (International Conference on Solid Compounds of Transition Elements) in 2016, both held in Zaragoza. Effectively Juan has led a marked number of projects and cooperative actions, from the Aragon region, Spain up to the European level. Besides he has established solid international and fruitful cooperative links with research a lot of teams namely in France, Italy, Netherlands, Poland, Romania, and Ukraine… 4. Epilogue Gifted with a pleasant character, the hard worker and efficient researcher Juan Bartolomé has no difficulty to convince as well his peers, his colleagues and young students to collaborate with him. Juan Bartolomé is recognized as a master magnetist and thermodynamicist, exactly working in the footsteps of the founders Blas Cabrera, Cornelius Jacobus Gorter, and Louis Néel. ________ UNESCO Archives AtoM Catalog (pp. 57–59). https://atom.archives.unesco.org/reunion-detudes-sur-le-magnetisme-organisee-en-collaboration-avec-le-service-central-de-la-recherche-scientifique-champ-moleculaire-aimantation-a-saturation-et-constantes-de-curie-des-elements-de-transition-et-de-leurs-alliages-raport-?sf_culture=fr